Performance and exhaust emissions of a gasoline engine using artificial neural network - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This study deals with artificial neural network (ANN) modelling of a gasoline engine to predict the brake specific fuel consumption,. brake thermal efficiency, exhaust gas temperature and exhaust emissions of the engine. To acquire data for training and testing the proposed ANN, a four-cylinder, four-stroke test engine was fuelled with gasoline having various octane numbers (91, 93, 95 and 95.3), and operated at different engine speeds and torques. Using some of the experimental data for training, an ANN model based on standard back-propagation algorithm for the engine was developed. Then, the performance of the ANN predictions were measured by comparing the predictions with the experimental results which were not used in the training process. It was observed that the ANN model can predict the engine performance, exhaust emissions and exhaust gas temperature quite well with correlation coefficients in the range of 0.983-0.996, mean relative errors in the range of 1.41-6.66% and very low root mean square errors. This study shows that, as an alternative to classical modelling techniques, the ANN approach can be used to accurately predict the performance and emissions of internal combustion engines. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: artificial neural network; gasoline engine; octane number; exhaust emissions; CONDENSER; SYSTEM